2021
DOI: 10.1136/bmjdrc-2021-002174
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of breath test for diabetes mellitus diagnosis: a systematic review and meta-analysis

Abstract: The review aimed to investigate the accuracy of breath tests in the diagnosis of diabetes mellitus, identify exhaled volatile organic compounds with the most evidence as potential biomarkers, and summarize prospects and challenges in diabetic breath tests. Databases including Medline, PubMed, EMBASE, Cochrane Library and Science Citation Index Expanded were searched. Human studies describing diabetic breath analysis with more than 10 subjects as controls and patients were included. Population demographics, bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In this study, ROC analysis showed an excellent discriminative property, with an AUC > 0.90 [66], for an ExA cutoff = 496 ppbv. This diagnosis accuracy in HF was largely higher that the moderate diagnosis accuracy reported in diabetes (AUC = 0.79 (95% CI 0.75-0.82) [67]). Yet, it was not assessed in intent-to-diagnose population study, because from the 235 HF outpatients screened, 89 were finally included.…”
Section: Exhaled Acetone In Heart Failure Patients: a Diagnostic And ...mentioning
confidence: 59%
“…In this study, ROC analysis showed an excellent discriminative property, with an AUC > 0.90 [66], for an ExA cutoff = 496 ppbv. This diagnosis accuracy in HF was largely higher that the moderate diagnosis accuracy reported in diabetes (AUC = 0.79 (95% CI 0.75-0.82) [67]). Yet, it was not assessed in intent-to-diagnose population study, because from the 235 HF outpatients screened, 89 were finally included.…”
Section: Exhaled Acetone In Heart Failure Patients: a Diagnostic And ...mentioning
confidence: 59%
“…In general, most studies on diabetes diagnosis rely on breath analysis of human subjects by using machine learning systems, achieving an accuracy of over 90% in distinguishing healthy individuals and patients. [ 21 ] However, the sensor platforms in previous studies mainly utilize semiconductor sensors with low response and high‐temperature requirements. Furthermore, gas samples from cells, organs, and mice contain considerably less gas volume than human breath samples.…”
Section: Resultsmentioning
confidence: 99%
“…Another source of acetone is the alcohol dehydrogenase enzyme, which reversibly converts isopropyl alcohol to acetone via an oxidation-reduction reaction [31]. This interaction implies that acetone is directly correlated to isopropyl alcohol and these two VOCs usually co-exist [11,31,32]. These two VOCs are associated with cellular metabolic dysregulation.…”
Section: Discussionmentioning
confidence: 99%